2018
DOI: 10.3390/ma11091569
|View full text |Cite
|
Sign up to set email alerts
|

Porous Silicon-Based Catalysts for the Dehydration of Glycerol to High Value-Added Products

Abstract: Increasing worldwide biodiesel production has led to the generation of an important glycerol surplus, which needs to be valorized in order to improve the economic and environmental sustainability of the biodiesel industry. In this context, glycerol dehydration to acrolein by acid catalysis appears to be a potential route of glycerol valorization, since acrolein is an important intermediate for many chemical industries. The main drawback of this catalytic process is catalyst deactivation. Different alternatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 91 publications
(130 reference statements)
2
9
0
1
Order By: Relevance
“…Proses fase gas lebih unggul disebabkan oleh sifat heteropolyacids dengan keasaman Brönsted yang kuat menunjukkan aktivitas katalitik awal yang baik , dehidrasi fase gas gliserol memiliki kondisi reaksi ringan [12]. Dehidrasi gliserol membutuhkan asam kondisi, karena protonasi gliserol menyebabkan penurunan penghalang energi aktivasi dari sekitar 60 hingga 20 KJ mol -1 [13]. Katalis padat memiliki aktivitas dan stabilitas yang dapat diterima ketika air berperan sebagai reaktan atau produk [14].…”
Section: Pendahuluanunclassified
“…Proses fase gas lebih unggul disebabkan oleh sifat heteropolyacids dengan keasaman Brönsted yang kuat menunjukkan aktivitas katalitik awal yang baik , dehidrasi fase gas gliserol memiliki kondisi reaksi ringan [12]. Dehidrasi gliserol membutuhkan asam kondisi, karena protonasi gliserol menyebabkan penurunan penghalang energi aktivasi dari sekitar 60 hingga 20 KJ mol -1 [13]. Katalis padat memiliki aktivitas dan stabilitas yang dapat diterima ketika air berperan sebagai reaktan atau produk [14].…”
Section: Pendahuluanunclassified
“…Acrolein is the target product of glycerol dehydration. Although most authors (e.g., [4,5] review papers) have indicated that Brønsted acid sites are responsible for the reaction pathway leading to acrolein formation via 3-hydroxypropanal intermediate product, whereas Lewis acid sites activate dehydration of glycerol to hydroxyacetone, one has to take into account that LAS can be transformed to pseudo-Brønsted acid sites in the presence of H 2 O in the reaction medium [35]. Therefore, in the analysis of activity and selectivity in glycerol dehydration, both BAS and LAS should be taken into account.…”
Section: Glycerol Dehydrationmentioning
confidence: 99%
“…For many years, various research groups have been working on different catalytic transformations of glycerol to desired target products [1][2][3]. One of the possible catalytic routes for glycerol transformation is its dehydration to acrolein [4] and oxidehydration to acrylic acid [5]. Acrolein is a versatile intermediate that is largely employed in the chemical industry, among others, for the production of acrylic acid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations